Effect of slug mycophagy on Tuber aestivum spores. Issue 10 (October 2021) - Ori, Francesca; Menotta, Michele; Leonardi, Marco; Amicucci, Antonella; Zambonelli, Alessandra; Covès, Hervé; Selosse, Marc-André; Schneider-Maunoury, Laure; Pacioni, Giovanni; Iotti, Mirco
Abstract: Truffles in the genus Tuber produce subterranean fruiting bodies that are not able to actively discharge their spores in the environment. For this reason, truffles depend on mycophagous animals for reproduction. Fungus consumption (mycophagy) is a behaviour typical of both vertebrates and invertebrates. Mammals, especially rodents, are the most studied group of mycophagists and have been found to consume a great variety of fungi. Among invertebrates, mycophagy is documented in arthropods, but rarely in molluscs. In our study we assessed the effect on the morphology and mycorrhizal colonization of Tuber aestivum spores after passage through the gut of slugs ( Deroceras invadens ) and, for comparison, of a house mouse ( Mus musculus ). Light, scanning electron and atomic force microscopy revealed that the digestion, especially by slugs, freed spores from the asci and modified their morphology. These are believed to be the reasons why we observed an improvement in oak mycorrhization with the slug and rodent ingested spores in comparison to a fresh spore inoculation. We also demonstrated by molecular barcoding that slugs' guts sampled on a Tuber melanosporum truffle ground contain spores from this species and Tuber brumale, further suggesting that some invertebrates are efficient Tuber spore dispersers. Highlights: The ingestion of spores by slugs causes the complete disruption of asci. SEM and AMF analyses showed that after slug digestion the spore wall is partially degraded. Slugs collected on truffle ground contain Tuber spores detectable by molecular barcoding. The passage of Tuber spores through the gut of slugs promotes mycorrhizal infection of Quercus robur seedlings.